2017
DOI: 10.1007/s10517-017-3685-2
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Intraoperative Blood Loss during Total Knee Arthroplasty in HCV+ and HCV- Patients with Hemophilia A

Abstract: We examined HCV+ and HCV- hemophilia A patients with knee arthropathy and hematocrit above 38.5%. The mean density of erythrocytes was studied by the phthalate method, intraoperative blood loss was assessed gravimetrically. The volume of blood loss in HCV+ patients with manifest adhesive process and chronic synovitis varied from 300 to 1900 ml, in patients with moderate adhesive process from 400 to 1500 ml. The volume of blood loss in HCV- patients was 300-800 ml. A positive correlation between the blood loss … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…There have been few studies on risk factors for PBL in patients with haemophilia. Although preoperative haematocrit of <38.5%, increased erythrocyte density and HCV infection were reported as risk factors, 2,4 the methods used to assess blood loss in these studies were not accurate because they failed to measure hidden blood loss. Additionally, independent risk factors were not analysed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There have been few studies on risk factors for PBL in patients with haemophilia. Although preoperative haematocrit of <38.5%, increased erythrocyte density and HCV infection were reported as risk factors, 2,4 the methods used to assess blood loss in these studies were not accurate because they failed to measure hidden blood loss. Additionally, independent risk factors were not analysed.…”
Section: Discussionmentioning
confidence: 99%
“…Shurkhina et al reported that intraoperative blood loss during TKA increases in patients with haemophilic arthropathy when haematocrit levels are lower than 38.5%, 2 hepatitis C virus (HCV) is positive and erythrocyte density is high. 4 Although increased blood loss is an important factor that has the potential to affect the clinical outcome after TKA, 5,6 there have been no additional studies analysing the risk factors for increased blood loss after TKA for haemophilic arthropathy of the knee. Furthermore, these aforementioned studies calculated blood loss during surgery using the weight of pre-and postoperative cloths and the volume of blood in a suction pump, which failed to assess for any hidden blood loss.…”
Section: Introductionmentioning
confidence: 99%